Zero-Carbon Energy Kyoto 2012 Special Edition of the Joint Symposium "Energy Science in the Age of Global Warming" of the Kyoto University Global COE Program and the JGSEE/CEE-KMUTT - Yao, Takeshi.; Yao, Takeshi. (Green Energy and Technology, 2013)
This is the final year of the 5-year Global COE (Center of Excellence) Program "Energy Science in the Age of Global Warming – Toward a CO2 Zero-Emission Energy System" of the Ministry of Education, Culture, Sports, Science and Technology of Japan. This program aims to establish an international education and research platform to foster educators, researchers, and policy makers who can develop technologies and propose policies for establishing a scenario toward a CO2 zero-emission society no longer dependent on fossil fuels, by the year 2100. Since 2008, four departments of Kyoto University—the Graduate School of Energy Science, the Institute of Advanced Energy, the Department of Nuclear Engineering, and the Research Reactor Institute—have joined together to engage in the management of the Program. The Fourth International Symposium of the Global COE, titled “Zero-Carbon Energy, Kyoto 2012,” was held jointly with the Joint Graduate School of Energy and Environment / Center of Excellence on Energy Technology and Environment (JGSEE/CEE) at King Mongkut's University of Technology, Thonburi (KMUTT) in Bangkok, Thailand in May 2012. This book is a compilation of the lectures and presentations from the symposium. Securing energy and conservation of the environment are the most important issues for the sustainable development of human beings. The energy problem cannot be simply labeled a technological one, as it is also deeply involved with social and economic elements, and it is essential to establish low carbon-energy science as an interdisciplinary field.